JURNAL: Partisipasi Pemerintah Dalam Menangani Dampak Perekonomian Negara Dimasa Pandemi - Fajar Nursobah (Universitas Slamet Riyadi, 2022)
ABSTRACT Indonesian financial expert, lecturer at the Faculty of Economics and Business, admits that the 2020 state of emergency is the biggest and most deplorable one, causing a welfare crisis and also causing significant monetary losses. Practically all areas are affected, and the area most travel industry area because the business ended due to social removal. Meanwhile in the monetary sector, there is a danger that the business district will not be able to make credit installments. In this way, OJK screens useful areas that are generally affected by Covid-19. Although the financing arrangements for beneficial regions are around 28-30%, while the wasteful financing is around 70-72%, the regions that have a multiplier impact on the economy outweigh the destructive ones. This is done to expand the versatility of the business world in the midst of the Covid-19 pandemic. This series is due to the total lack of interest from the local area and affects the two regions, also affecting different areas, for example transportation and automotive areas due to reduced human portability, mining areas due to the creation of abundance, development areas due to the potential for changing events and MSME areas. `In the 1998 monetary emergency, MSMEs became the guardian angels for the Indonesian economy, but in the current public welfare emergency, MSMEs are the ones who feel the most impact. Based on information from the Indonesian Chamber of Commerce and Industry, there are 6 million workers affected and 90% are on leave, while the rest have been laid off. The «State Must Be Present» is carried out with the Social Safety Net program which is completed by the public authorities because it is a form of responsibility to the regions. Some of the projects carried out are social assistance, acceleration of the implementation of Pre-Employment Cards and cutting electricity bills. The financial support given by the public authorities to overcome the Covid-19 pandemic amounted to Rp. 405.1 trillion which will be given to welfare areas in the amount of Rp. 75 trillion for the purchase of clinical equipment, worker welfare insurance, working limits for referral medical clinics. Meanwhile, for social protection, Rp. 110 trillion which is used for 10 million PKH recipients, 20 million basic food cards, 5.6 million pre-employment card recipients, as well as incentives for mortgage installments for Low- Income Communities and discounts on subsidized electricity rates.s. The Ministry of Finance, through the media briefing 'Tanya BKF' presented the Head of the Fiscal Policy Agency, Febrio Kacaribu, as the main resource person to discuss 'PEN and Other Fiscal Issues'. The inaugural conference, which was broadcast live through the Ministry of Finance's YouTube channel, was attended by more than 40 participants from the press. «The current state of the pandemic we are facing is similar to the Spanish Flu that occurred 100 years ago. The crisisfaced, of course, is also differentfrom the crises that have existed sofar. The PEN program itself is regulated in PP 23/2020 as the implementation of Article 11 of PERPU 1/2020.